Transdermal Delivery of Adriamycin to Transplanted Ehrlich Ascites Tumor in Mice - Ryoichi Matsuda; Yoshiaki Nonomura; Masataka Shiozuka (MDPI AG, 2013)
There is considerable interest in the skin as a site of anti-cancer drug application. Nevertheless, the skin poses a formidable barrier to drug penetration, thereby limiting topical and transdermal bioavailability. However, we previously showed that a thioglycolate-based depilatory agent increases the drug permeability of mouse skin. In the present report, we investigated the skin permeability and efficacy of the anti-cancer drug adriamycin increased when administered transdermally to mice in combination with a thioglycolate-based depilatory agent. Adriamycin in combination with depilatory treatment reduced Ehrlich tumor growth in hairless mice about the weight and size of harvested tumors. In addition, our delivery method for adriamycin increased the therapeutic effectiveness of this agent by decreasing toxicity. Moreover, measurement of adriamycin autofluorescence revealed that topically applied adriamycin penetrate the dermis after depilatory agent treatment. These results indicate that the transdermal delivery of anti-cancer drugs is feasible by handy pretreatment of the skin with a thioglycolate-based depilatory agent.